2011
DOI: 10.1016/j.nano.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nanoparticle trafficking across MDCK-II

Abstract: Polystyrene nanoparticles (PNP) cross rat alveolar epithelial cell monolayers via non-endocytic transcellular pathways. To evaluate epithelial cell type-specificity of PNP trafficking, we studied PNP flux across Madin Darby canine kidney cell II monolayers (MDCK-II). Effects of calcium chelation (EGTA), energy depletion (sodium azide (NaN 3 ) or decreased temperature), and endocytosis inhibitors methyl-β-cyclodextrin (MBC), monodansylcadaverine and dynasore were determined. Amidine-modified PNP cross MDCK-II 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
7
43
0
Order By: Relevance
“…Although it is possible to image live cells, it is difficult to gain detailed information about subcellular structures due to the limited spatial resolution. Nanoparticles which have been labeled by fluorescent dyes have been extensively studied and Confocal Laser Scanning Microscopy (CLSM) is an invaluable tool for the visualization of nanoparticles for in vitro studies [19][20][21][22] . By the use of these fluorescent based techniques, fluorescent emmission of nanoparticles and the subcellular location of nanoparticles have been determined.…”
Section: Intracellular Trafficking Of Nanoparticles Ros Production Amentioning
confidence: 99%
“…Although it is possible to image live cells, it is difficult to gain detailed information about subcellular structures due to the limited spatial resolution. Nanoparticles which have been labeled by fluorescent dyes have been extensively studied and Confocal Laser Scanning Microscopy (CLSM) is an invaluable tool for the visualization of nanoparticles for in vitro studies [19][20][21][22] . By the use of these fluorescent based techniques, fluorescent emmission of nanoparticles and the subcellular location of nanoparticles have been determined.…”
Section: Intracellular Trafficking Of Nanoparticles Ros Production Amentioning
confidence: 99%
“…We think this is a reasonable result because cationic nanoparticles have been reported to strongly interact with the negatively charged region of the cell membrane surface via electrostatic forces. 36,38) In addition, we observed that the cellular associated amount of magnetic liposomes at 37°C was much higher than that at 4°C, and the highest quantitative change between 37 and 4°C was observed with magnetic cationic liposomes (Fig. 3).…”
Section: Discussionmentioning
confidence: 79%
“…We have reported that translocation of polystyrene nanoparticles across RAECM and Madin Darby canine kidney type II cell monolayers (MDCK-II) was not decreased in the presence of 10-200 µM methyl-β-cyclodextrin. 30,32 Clathrin is composed of three light and three heavy chains that form a triskelion. Assembly of the triskelion leads to formation of a net-like basket (clathrin-coated pit) at the cell plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…To explore if quantum dot translocation across RAECM involves endocytotic mechanisms, methyl-β-cyclodextrin, chlorpromazine, and dynasore were used to disrupt lipid raft-mediated endocytosis, 30,32,36,37 clathrin-mediated endocytosis, 30,38 and dynamin-dependent endocytosis (including clathrin-mediated and caveolin-mediated endocytosis), 30,32,39 respectively. Briefly, RAECM were pretreated for 30 minutes with methyl-β-cyclodextrin (200 µM, Sigma), chlorpromazine (28 µM, Sigma), or dynasore (80 µM, Sigma) in both apical and basolateral fluids.…”
Section: Effects Of Endocytosis Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation